DISTANCE LEARNING OF STUDENTS AS A CHALLENGE FOR THE OVERALL EDUCATIONAL PROCESS - Рідель, Тетяна (SWorldJournal, 2023)
The article examines the problem of organizing distance learning in conditions of uncertainty and the forced transition of teachers and students to online interaction. The situation that has arisen is considered as a natural experiment in which the educat